Predicting global QoL after orthotopic neobladder or ileal conduit diversion: nomogram development - Siracusano, Salvatore; Zaka, Agustina; Zaffuto, Emanuele; Porcaro, Antonio Benito; Colombo, Renzo; Talamini, Renato; Romantini, Federico; Montorsi, Francesco; Lonardi, Cristina (Frontiers in Oncology, 2023)
Introduction Quality of life (QoL) outcomes in patients undergoing radical cystectomy (RC) with orthotopic neobladder (ONB) or ileal conduit (IC) has been extensively investigated. However, a general lack of consensus on QoL’s predictive factors exists. Aim of study was to develope a multivariable prediction model of global QoL outcome in patients with localized muscle-invasive bladder cancer (MIBC) undergoing RC with ONB or IC urinary diversion (UD). Methods A cohort of 319 patients who underwent RC and ONB or IC urinary diversion were retrospectively enrolled. Multivariable linear regression analyses were used to predict the global QoL score of the European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire (EORTC QLQ-C30), according to the patient characteristics and UD. A nomogram was developed and internally validated. Results The two patients’ groups significantly differed with regards to comorbidities profiles (chronic cardiac failure: p<0.001; chronic kidney disease: p<0.01; hypertension: p<0.03; diabetic disease: p=0.02; chronic arthritis: p=0.02). A multivariable model that included patient age at surgery, UD, chronic cardiac disease and peripheral vascular represented the basis for the nomogram. The calibration plot of the prediction model showed a systematic overestimation of the predicted global QoL score over the observed scores, with a slight underestimation for observed global QoL scores between 57 and 72. After performing leave-one-out cross validation the root mean square error (RMSE) emerged as 24.0. Discussion/Conclusions A novel nomogram based completely on known pre-operative factors was developed for patients with MIBC undergoing RC to predict a mid-term QoL outcome.